Brill's companion to episodes of 'heroic' rape/abduction in classical antiquity and their reception - Lauriola, Rosanna (Brill, 2022)
"Sexual violence is one of the oldest and most difficult problems of humankind. Many of the "love stories" in Classical Greek and Roman Myth are tales of rape, a fact that is often casually glossed over in both popular and scholarly treatments of these narratives. Through a careful selection of stories, this book provides a deep exploration of rape in Classical Myth as well as in the works of art and literature that have responded to it through the millennia. The volume offers an essential reading for anyone who wishes to understand sexual violence from different perspectives and through an interdisciplinary approach, which includes Trauma Theory and Evolutionary Psychology"--
Keywords: Mythologie; Sexualisierte Gewalt -- Motiv; Römisches Reich; Griechenland -- Altertum; Rape in literature; Abduction in literature; Classical literature / History and criticism; Classical literature / Appreciation; Classical literature / Influence